Партнерство як основа конкурентоспроможності розвитку громад в умовах децентралізації - Ортіна, Ганна Володимирівна; Ортина, Анна Владимировна; Ortina, Hanna; Єфіменко, Людмила Миколаївна; Ефименко, Людмила Николаевна; Yefimenko, Liudmyla (My University, 2019)
UK: У статті зроблена спроба аналізу тенденції розвитку економіки через конкуренцію та партнерство, запропоновано переваги впровадження партнерства. Уточнено роль держави у сталому розвитку громад. Проаналізовано проблему конкуренції та партнерства з точки зору сталого розвитку. Наведено процес формування сталого розвитку громад через партнерство як складової державної політики та пріоритетного напрямку розвитку економіки, а також як результат партнерства між громадами задля сталого розвитку економіки держави. Розглянуто реалізація сталого розвитку громад яка передбачає необхідність пошуку нових локомотивів зростання економіки шляхом розвитку партнерства між секторами суспільства та залучення до планування, розробки та реалізації усіх зацікавлених сторін, оскільки лише шляхом спільного розв'язання нагальних проблем можливо забезпечити успішну реалізацію зазначеної стратегії. EN: The article attempts to analyze the tendencies of economic development through competition and partnership, and suggests the advantages of implementing the partnership. The role of the state in the sustainable development of communities is specified. The problem of competition and partnership in terms of sustainable development is analyzed. The prospects for the development of decentralization and partnership processes in Ukraine are outlined in the light of the complex demographic situation. The process of formation of sustainable development of communities through partnership as a component of state policy and a priority direction of economic development, as well as the result of partnership between communities for the sustainable development of the state economy, is presented. The essence of the idea of urbanization, which is the organization of cooperation between urban and rural areas on the basis of mutually beneficial cooperation, distribution of powers, use of existing advantages in order to bring rural areas closer to sources of concentration of innovation, social and financial capital, investments, to objects of social, transport infrastructures inherent in urban settlements, along with more active involvement of resources, which are rich in rural areas, in the processes of social production. The basic principles on which cooperation is based, namely: legality, voluntariness, mutual benefit, transparency and openness, equality of participants, mutual responsibility of the subjects of cooperation for its results. The implementation of sustainable community development is considered, which involves the necessity of finding new locomotives for economic growth by developing partnerships between the sectors of society and involving them in the planning, development and implementation of all stakeholders, as it is only through the joint resolution of urgent problems that it is possible to ensure the successful implementation of the strategy.
Partnership as a basis for the competitiveness of community development in conditions of decentralization
Keywords: конкуренція; партнерство; державна політика; інноваційна система; ресурс; competition; partnership; state policy; innovation system; resource